PENDIDIKAN KEAGAMAAN PADA KELUARGA PADEDE BULAENG - Rosdiana Rosdiana (EDUCANDUM, 2017)
This research seeks to know the picture about the reality of religious education in thefamily of craftsmen both in the family environment and religious social interactionamong fellow craftsmen. This research is qualitative research. Family craftsmen aredetermined on the basis of family representation by considering the families ofcraftsmen directly doing production activities. Data collection techniques areconducted through interviews and observation. The results showed that religiouseducation conducted by the craftsmen family is through the transfer of religious valuesin which a person grows and becomes part of a family, such as the value of aqidah,shariah, and moral values. These religious values are taught in the family by directexample, habituation, message, and supervision at all times and opportunities